Low Cost Flood Alert via SMS - Mohd Azlan, Ahmad Zarron (UTeM, 2010)
The Low Cost Flood Alert via SMS is designed to give an early warning to user who lives near the flood area. The system is designed based on the current system but there have a certain part was modified to reduced the cost of the system. The system consists of PIC, sensors circuit, power supply and alarm system. The sensors used for detecting the level of water or river during the flood season. Then, the PIC will act as controller which is received the analog signal from the sensor and convert it into digital signal to input GPRS module and alarm system. When the system senses the existences of water, it automatically turns the alarm and emergency light on. Besides that, the GPRS module also triggered to send the text message to inform the user about the flood parameter. In other word, it gives an early warning to the users about the dangerous situation during the flood disaster.